Forensic pharmacy: topical questions of the involvement of the joint forensic test for establishing the real cause of death in a road accident as guarantee of the correct qualification of culprit`s behavior in a criminal trial - Abrosymov, Oleksandr; Abrosymova, Oleksandra; Sichkarenko, Oleksandr (Actual Problems of Medicine and Pharmacy, 2021)
The article deals with trends of road traffic safety issues on Ukraine`s roads in 2017-2019 which bring about the necessity of a more detailed approach to the correct qualification of culprits` behaviour according to Article 286 of The criminal code of Ukraine depending on the severity of the bodily harm and the cause of death when it is difficult to determine it in case of a combined trauma of an elderly person that suffers from a serious age-related disease and/or has morphological traits of the body, who had received neither proper treatment nor preventive control, providing the diagnosis had been established by the hospital unfully, after which the person died with a huge time gap. The approach that utilizes additional opportunities given by the Joint forensic test for objectivation of a death cause.